Fabrication of cellulose-based dielectric nanocomposite film with excellent energy storage performance via codissolution-regeneration method. (February 2023) - Zhang, Sufeng; Liu, Jiaqi; Guo, Qing; Wei, Ning; Ning, Yating; Bai, Yuhan; Tian, Ye; Wang, Tong; Sun, Zixiong; Pu, Yongping
Highlights: Cellulose-based dielectric nanocomposite film for energy storage capacitors were fabricated via codissolution-regeneration method. The highly energy storage density over 8 J/cm 3 of such cellulose-based matrix film is due to robust hydrogen bonds between PVDF and cellulose molecules. A uniform cellulose/PVDF-BT ternary film with high breakdown strength (3.70 MV/cm) and a giant energy storage density (10.81 J/cm 3 ) were achieved. Both good mechanical property and hydrophobicity were achieved with the aid of hydrogen-bonding environment modulating. Finite element simulation of breakdown behavior demonstrates the superiority of this composite. Abstract: The extensive use of petroleum-based dielectric composites has caused many environmental problems, which has forced us to turn our attention to biodegradable materials. In this study, cotton cellulose and PVDF were codissolved and regenerated as a matrix film in an elaborate way, and barium titanate (BT) nanoparticles were added to ensure high energy storage performance. Strong hydrogen bonds formed between the fluorine atoms of PVDF and the abundant hydroxyl groups of cellulose molecules, which were more robust than their own intramolecules; these strong hydrogen bonds promoted polarization intensity, thus improving the energy storage density of the matrix (from 6.50 J/cm 3 @3.20 MV/cm of pristine PVDF film to 8.29 J/cm 3 @3.20 MV/cm). Upon the addition of BT nanofillers, the cellulose/PVDF-BT ternary film exhibited an impressive breakdown strength (3.70 MV/cm) and a giant energy storage density (10.81 J/cm 3 ). In addition, the composite film possessed excellent tensile strength (∼60 MPa). The electrical breakdown behavior was confirmed and visualized by finite element simulation. Significantly, our work has instructive implications for fabricating flexible energy storage devices based on renewable bioresources.